The influence of integrity awareness in business on entrepreneurial traits among entrepreneurs in Kuching. - Mohd Azan Haizul Mohamad Mayling. (2017)
Integrity always relates to business ethics. It has been defined in a variety of ways. Prior scholar relates integrity with moral consistency, trust and honest. Whether big or small the business integrity is a critical concept that may lead to long-term success and sustainability. This paper emphasizes the integrity of the individual and its importance to create the culture of integrity through identifies the influence of integrity awareness in business on entrepreneurial traits among entrepreneurs in Kuching. The mission of this paper is to determine the existence of the relationship between the influence of integrity awareness and entrepreneurial traits. The Personality Trait Theory is applicable to support the variable of the study. From the survey conducted among registered entrepreneurs using descriptive statistic, the finding indicates there is no relationship between influence of integrity awareness and entrepreneurial traits. Integrity should be literally the practice of good ethics to enhance entrepreneur’s character to undergo the business transaction to be fair and transparent. However, this study indicated that integrity awareness did not influence traits of the entrepreneurs in Sarawak. This research had contributed to new perspectives of studies in the area of integrity and entrepreneurial trait.